Study on Management Practice and Challenges on Beekeeping in Bagnaskali, Palpa, Nepal - Nepali, Pit Bahadur; Saru, Apsara; Chokhal, Keshab; Rana, Hira Bahadur (Prāgyik Prabāha, 2023)
Beekeeping is the architectural design of hives to increase honey bee productivity. Research methods used between February to December 2021 in Bagnaskali Rural Municipality (Khanigaun and Barangdi), Palpa. This study's aims were to understand beekeeping management practice and investigate its challenges. Random sampling methods were employed by surveys, interviews, and field observations. Throughout the study period, semi-structured interviews with 30 household respondents were performed. They preferred modern hive than traditional hive which were placed backward side of house. Four times a year, respondents collect honey, producing high-quality honey products. The high demand for local honey, the distance to the market, the scarcity of bee colonies, disease outbreaks, etc. were the most frequent challenges in managing honey bee practices. In addition to these, biological pests and predators of honey bees in the current study area included wasps, spiders, ants, beetles, lizards, wax moths, and mites. This investigation adds to the body of traditional knowledge on beekeeping challenges and management. It is necessary to conduct more research on the local honeybee population or sample, diseases, pests, and predators.